2012
DOI: 10.1021/jp3060137
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Photodegradation Efficiency with Surface Potential of Silver-TiO2 Nanocomposite Thin Films

Abstract: The present work focuses on photocatalytic performance of Ag-TiO2 systems. Nanocrystalline thin films of TiO2-and Ag-doped TiO2 are grown by sol–gel method, followed by spin-coating technique on Si ⟨100⟩ surface. The crystallinity and crystal size were measured from X-ray diffraction and transmission electron microscopy studies. Lateral distribution of work function (WF) was examined through contact potential difference measurement done by scanning Kelvin probe microscopy. Local WFs of Ag-TiO2 thin films were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…5(a)]. Thus WF of pristine TiO 2 thin film was estimated to be 5.035 eV corresponding to WF of reference Au tip as 5.1 eV [3]. The CPD value for 100 MeV Ag ion irradiated thin films increases from 113 mV to 460 mV for fluence varying from 1 × 10 12 ions cm −2 to 5 × 10 13 ions cm −2 .…”
Section: Skp Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…5(a)]. Thus WF of pristine TiO 2 thin film was estimated to be 5.035 eV corresponding to WF of reference Au tip as 5.1 eV [3]. The CPD value for 100 MeV Ag ion irradiated thin films increases from 113 mV to 460 mV for fluence varying from 1 × 10 12 ions cm −2 to 5 × 10 13 ions cm −2 .…”
Section: Skp Studiesmentioning
confidence: 96%
“…The measurement of CPD is carried out in terms of work function (WF) measurement using scanning Kelvin probe technique. The relation between WF and CPD (V CPD ) can be expressed as [3,27,28],…”
Section: Skp Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its high carrier transfer rate and plasmonic effect, Ag deposited on a TiO 2 surface successfully acts as a transfer intermediate for photogenerated electrons and holes, promoting charge carrier separation [15,16]. With a view toward controlling Ag particle size and dispersion, methods of sol-gel [17][18][19][20] and photodeposition [21,22] can be used since photocatalytic activity closely depends on content, crystal size, and morphology [23][24][25][26]. Specifically, Ag quantum dots and/or nanoclusters can effectively promote the separation of the photo-generated electrons and holes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the semiconductors employed, TiO 2 is most widely used because of its suitable flat band potential, chemical state, non-toxicity, strong oxidation capacity and also its high photocatalytic activity. However the use of TiO 2 is impaired by its wide band gap (∼3.2 eV), which requires UV light for photoactivation, and its major limitation is higher recombination rate of the photogenerated charge carriers resulting in lower quantum yield [2][3][4][5][6][7][8]. In this regard our research group had previously reported the incorporation of the paramagnetic Mn 2+ ions in anatase lattice at Ti 4+ substitution site [9].…”
Section: Introductionmentioning
confidence: 99%